Uji Aktivitas Antibakteri Ekstrak Etanol Daun Kemangi (Ocimum sanctum L) Sebagai Antibakteri Terhadap Streptococcus mutans - Rialita Lifiani*; Rezza Fikrih Utama; Ester Saripati Haria; Rahayu Kartini (Universitas Sari Mutiara Indonesia, 2022)
Background: One of the traditional medicinal plants that are widely used by the Indonesian people is the basil plant (Ocimum sanctum L). Which has a role as an antibacterial that can inhibit the growth of bacteria. Objectives: The Purpose of this study was to determine the ability of basil leaf extract (Ocimum sanctum L) to inhibit the growth of Streptococcus mutans bacteria from concentrations of 20%, 40%, 60%, 80% and to determine the effective concentration of antibacterial activity against the growth of Streptococcus mutans bacteria. Method: This research method used the experimental method. Antibacterial activity was tested by diffusion method using disc paper. The ethanol extract of basil leaves was made by maceration method using 96% ethanol as solvent. The concentration of the test solution used was a negative control DMSO, positive control of Chlorhexidine. Result: The results of the phytochemical screening test of basil leaf powder showed the presence of Flavonoid compounds, Steroids/Triterpenoids, tannins, and saponins. The results of the antibacterial activity test showed that the basil leaf extract gave inhibition zones at concentrations of 20%, 40%, 60%, and 80% against Streptococcus mutans bacteria, each of which had an inhibition zone (13,5mm), (16,6mm), (18mm), and (18,9mm) in Chlorhexidine 20,6mm. Conclusion: The conclusion from research results can be concluded that basil leaf extract (Ocimum sanctum L) has anti-Bacterial activity against Streptococcus mutans bacteria.